LAW AND MORALITY IN "HINDU DHARMA" - Manickam, T. M (Journal of Dharma, 1979)
The word " Law " as used in jurisprudence in the English language might find its counterpart in Sanskrit legal literature in more than one expression such as myoma, nydya, niti, and vidhi, all meaning fundamentally the same but with various shades of meaning with reference to specific contexts of the administration of legal justice. Their special nuances, when used with other related terms of the dispensation of justice, may be made clear here by just mentioning a few instances of "combinations such as niyamdvali (Statutes/Rules), . nyayasanam (Seat of His Majesty, the Judge), nitipitham (Seat of Justice/Court of Justice) and vidhtvacakam (Judicial Sentence). However, none of these expressions, singly or combined, conveys exactly what is meant by "Law" in the Hindu religion-moral tradition. Here it is the word "Dharma" that is used to speak about the sacred nature and function of the " Rules of life" of the people who lay claims to the Aryan religio-cultural heritage. These people seem to have made no clear-cut distinction between secular laws and sacred laws as applicable to two separate aspects of life. As life. was conceived to be one, whole unit its pattern of living was expressed in a unified" Way of life." This way of life, which should be a blend of the sacred and the secular they called the" Hindu Dharma", follows the" Rules of Dharma." So in this article I would prefer to call this heritage of living by their own favourite term " Hindu Dharma", rather than" Hinduism" or "Hindu tradition." "Hindu Dharma" means a complex reality of living.